Deflection gating for time-resolved x-ray magnetic circular dichroism–photoemission electron microscopy using synchrotron radiation - Wiemann, C.; Kaiser, A. M.; Cramm, S.; Schneider, C. M. (Review of scientific instruments, 2012)
In this paper, we present a newly developed gating technique for a time-resolving photoemission microscope. The technique makes use of an electrostatic deflector within the microscope's electron optical system for fast switching between two electron-optical paths, one of which is used for imaging, while the other is blocked by an aperture stop. The system can be operated with a switching time of 20 ns and shows superior dark current rejection. We report on the application of this new gating technique to exploit the time structure in the injection bunch pattern of the synchrotron radiation source BESSY II at Helmholtz-Zentrum Berlin for time-resolved measurements in the picosecond regime.